Attaining the millennium development goals in India - Deolalikar, Anil B. (New Delhi, 2005)
India has committed to attaining the Millennium Development Goals (MDGs) by the year 2015. The MDGs are a set of numerical and time-bound targets related to key achievements in human development launched at the Millennium Summit 2000. In the developmental context, they constitute the most widely-accepted yardstick of efforts made and policies implemented by governments, donors, and non-governmental organizations. Attaining the MDGs is imperative and especially so for a developing country such as India. Significant among these goals are: BL Halving of the child underweight rate (from its level in 1990) BL Halving the proportion of people who suffer from hunger BL Two-thirds reduction in infant mortality rates BL Universal primary schooling BL Complete elimination of gender disparities in schooling opportunities How likely is India to reach these targets? And what will it take--by way of policy interventions--to attain the goals? This report critically analyzes India's performance across five selected MDGs. It uses a variety of data sources to analyze past progress in social indicators, paying particular attention to the heterogeneity of progress across India's many states and sub-units. It establishes correlations between the millennium development outcomes and various policy interventions, and proceeds to project the likely evolution of the millennium development indicators through 2015 based on particular policy scenarios. The report concludes by assessing the prospects of India as a whole--above all its poorer states--attaining the five MDGs by 2015. In doing so, the report highlights the type and scale of interventions that will be needed to attain these goals.
Keywords: Economic development